Sago Crop Management Strategy Based on Local Wisdom in Southern Konawe Regency - Asis, Asis; Rianse, Usman; Abdullah, Weka Gusmiarty; Budiyanto, Budiyanto; Taridala, Siti Aida Adha; Geo, La Ode; Baka, Wa Kuasa (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This study aims to analyze the shape and existence of local wisdom in the development of sago and to analyze the development strategy of sago processing based on local wisdom in the Angata District, Konawe Selatan Regency. The research variables consisted of forms of local wisdom, strength factors, weaknesses, opportunities, and threats to the development of sago processing. Data were analyzed with SWOT analysis. The results showed that the form and existence of local wisdom in sago processing activities in the Angata District that were still maintained were the involvement of workers, the selection of sago tree stands, and the destruction of pellets. Meanwhile, the strategy of managing sago crops based on local wisdom in Angata District can be done by utilizing the potential of land availability, expanding the network and market absorption, forming capital cooperation, adopting technology, optimizing income and public awareness, the assertiveness of sago regulation, improving the quality of human resources farmers, as well as the preparation of instructors/advisors who are competent in the field of sago management.